Prinsip Maqosid Ash-Shariah Dalam Konsep Kebutuhan Islam - Muhammad Irkham Firdaus; Jaya Sahputra (STIS DAFA MATARAM, 2022)
This study aims to understand and analyze the concepts of needs and Maqashid alShariah through a library research approach. The method includes collecting data from primary literature such as classical and contemporary texts and the works of AlGhazali, as well as secondary sources like journal articles, books, theses, and dissertations. The research findings indicate that human needs, which are unlimited, should be met proportionally and balanced according to the principles of Maqashid al-Shariah, emphasizing the preservation of religion, life, intellect, lineage, and wealth. The contribution of this research is to provide a comprehensive understanding of how the concept of needs in Islam aligns with the principles of Maqashid al-Shariah to achieve individual and societal well-being.